Understanding the Effectiveness of Multicultural Education in Enhancing Social Studies Learning Outcomes - Charles Kapile (Westscience Press, 2024)
This research aims to explore the effectiveness of multicultural education in enhancing the learning outcomes of Social Studies (IPS). In an increasingly complex era of globalization, multicultural education becomes increasingly important in addressing the challenges of cultural and social diversity. Through the method of literature review, this research examines various relevant sources of data, including journal articles, books, and research reports related to multicultural education and IPS learning. The findings of the research indicate that multicultural education can significantly contribute to enhancing students' understanding of concepts in IPS by expanding students' perspectives and creating an inclusive learning environment. However, challenges in the implementation of multicultural education such as the lack of teacher training and resistance to curriculum changes also need to be addressed. Therefore, it is suggested that multicultural education be more integrated into the IPS curriculum, while teachers are provided with adequate training in implementing multicultural approaches in the classroom. Thus, this research provides a deep understanding of the importance of multicultural education in the context of IPS learning and provides a foundation for the development of more inclusive educational approaches in the future.